Disaster Relief Drivers: China and the US in Comparative Perspective - Wei, J.; Zhao, D.; Marinova, Dora (East Asian Institute, 2013)
The United States and China, as the largest developed country and the largest developing country in the world, respectively, have their own overt and covert influences on the world. This article discusses the foreign responses when the US was hit by the catastrophic Hurricane Katrina in 2005 and China by the Wenchuan earthquake in 2008. By using a three-stage process to describe disaster aid decisions, it was found that developed countries were more likely to grant disaster aid, but the scale of their assistance was not the largest. Evidence showed that countries were more likely to offer assistance if they were geographically located closer to the affected areas but this was not the case in decisions made on the type and amount of aid provided. Assistance from European countries, on the other hand, largely showed a form of cosmopolitan humanitarianism.